Best M-term orthogonal trigonometric approximations of the classes B Ωp,θ of periodic functions of many variables - Stasyuk, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
Order estimates of the best M-term orthogonal trigonometric approximations of the classes B Ωp,θ of multivariable functions in the metric of the space Lq are obtained for the case 1 < q < p < ∞.